Factors Influencing Visitor Satisfaction at Marina Beach, Kalianda District - Shafa Hayah; Yaktiworo Indriani; Firdasari (Jurnal Sains Terapan Pariwisata, 2026)
This study was conducted to address the need for a clear understanding of visitor satisfaction levels and the key determinants influencing satisfaction at Marina Beach, Kalianda District, South Lampung Regency. In the context of increasing competition among tourist destinations, identifying the core factors that shape visitor satisfaction is essential for improving service quality and destination competitiveness. Therefore, this study aims to measure visitor satisfaction and determine the dominant factors affecting it. A survey method was applied to 70 visitors. Visitor satisfaction was analyzed using the Customer Satisfaction Index (CSI), while factor analysis was employed to identify the dominant influencing factors. The results indicate “satisfied”, with a CSI score of 77,10%. Five dominant factors were identified: accessibility and security; public facilities; information and services; comfort and attractiveness; and entertainment and attractions. These findings demonstrate that improvements in accessibility, security, and supporting facilities will yield the most significant impact on enhancing visitor satisfaction. The results provide an empirical basis for prioritizing resource allocation and strengthening Marina Beach’s competitive position as a sustainable tourism destination